Minority shareholder protection in group of companies and its effect on the economic growth : the case of Slovenia - Rozman, Til (LeXonomica, 2021)
Building on some of the key findings of the so-called law matters theory and its criticism, and taking into account that the economic growth of the Slovenian economy is weak, this paper emphasizes the importance of the minority shareholder protection for the economic growth. Since a group of companies has become the prevailing form of large enterprises, the focus of the paper is on the outside minority shareholder protection. Although groups of companies are a well-known and established topic in several law sectors at the national and the EU level (competition law, tax law, labour law etc.), they are only seldom the subject of the national or EU company law. However, Slovenia is one of only a few member states that have codified company law relating to group of companies. This paper finds that Slovenian normative framework provides a comprehensive protection for outside minority shareholder. As it is especially the enforcement matters that are relevant, not only the codified law (in books), further research on the Slovenian company law relating to group of companies is legitimate and necessary, and should revolve around the question of whether the regulation has achieved the desired objectives in the practice. Varstvo manjšinskih delničarjev v koncernu ter učinek na gospodarsko rast : primer Slovenije. Izhajajoč iz nekaterih ključnih ugotovitev in kritik t. i. teorije law matters ter ob upoštevanju dejstva, da je gospodarska rast v Republiki Sloveniji šibka, predmetni prispevek poudarja pomen varstva manjšinskih delničarjev za gospodarsko rast. Glede na ekonomsko realnost, da je koncern postal prevladujoča oblika velikih podjetij, se prispevek osredotoča na varstvo zunanjih manjšinskih delničarjev. Četudi nekatera pravna področja na nacionalni in EU ravni urejajo posamezna vprašanja v zvezi s koncerni (konkurenčno pravo, davčno pravo, delovno pravo itd.), so ti le redko predmet nacionalnega ali EU prava družb. Slovenija je ena redkih držav članic, ki je kodificirala koncernsko pravo (družb). Predmetni prispevek ugotavlja, da slovenski normativni okvir zagotavlja obsežno varstvo zunanjim manjšinskim delničarjem. Ker pa ni relevantno zgolj kodificirano pravo (v teoriji), temveč je pomembno zlasti izvajanje prava v praksi, je upravičeno in potrebno nadaljnje raziskovanje slovenskega koncernskega prava, in sicer zlasti z vidika vprašanja, ali so doseženi željeni učinki koncernskega prava v praksi. This paper is one of the outcomes that resulted from the fundamental research project funded by the Slovenian Research Agency: “Legal and Economic Aspects of Corporate Governance in the Public and Private sector as a Tool for Overcoming Economic and Development crisis”.